Preface - Pęcherski, R. (Archives of Mechanics, 2013)
This issue of the Archives of Mechanics contains a selection of papers presented at the 38th Solid Mechanics Conference (SolMech 2012) held in Warsaw, August 27–31, 2012. The series of Solid Mechanics Conferences have been organized by the Institute of Fundamental Technological Research of the Polish Academy of Sciences since 1953. The aim of the meetings is to bring together the researchers from different countries and offer them the possibilities for the presentation of scientific results from a wide area of solid mechanics.